RESPECT AND ETIQUETTE ROUTINES THE JAVANESE AND WESTERN CONCEPT OF SUNGKAN: A COMPARATIVE STUDY - Sukarsih, Ni Nyoman Tri (LPPM Universitas Dhyana Pura, 2021)
ABSTRACTCulture can be described through languages. The culture in western country is slightly differentfrom the one in eastern. The differences and similarities can be seen from their etiquettebehaviour, daily routines, etc. After finding Respect and Etiquette routines the Javanese conceptof Sungkan in Indonesia which represent eastern culture and good manners in Australia thatrepresent western culture. They have some differences and similarities. Australians have atradition of denigrating people who are achieve status for some reason other than sport. Theydo not have a culture similar to Javanese where respect is something separate and ingrained. .Inspecific situation western culture has the similarities to eastern, in this case the Indonesianespecially Javanese has a special. Emotional attitude of this kind is so elaborate. The peoplefrom lower class that is called caste or the younger people are taught to be Sungkan to upperclass and older people and it is untranslatable.Key words: Respect, etiquette, sungkan, good manners.ABSTRAKBudaya dapat digambarkan melalui bahasa. Budaya di negara barat sedikit berbeda dari yangada di timur. Perbedaan dan kesamaan dapat dilihat dari perilaku etiket mereka, rutinitas seharihari,dll. Setelah menemukan Respect and Etiquette rutin konsep Jawa Sungkan di Indonesiayang mewakili budaya timur dan sopan santun di Australia yang mewakili budaya barat.Mereka memiliki beberapa perbedaan dan kesamaan. Orang Australia memiliki tradisimerendahkan orang-orang yang mencapai status untuk beberapa alasan selain olahraga. Merekatidak memiliki budaya yang mirip dengan bahasa Jawa di mana rasa hormat adalah sesuatuyang terpisah dan mendarah daging. . Dalam situasi tertentu budaya barat memiliki kesamaandengan timur, dalam hal ini orang Indonesia khususnya Jawa memiliki keistimewaan. Sikapemosional semacam ini sangat rumit. Orang-orang dari kelas bawah yang disebut kasta atauorang muda diajarkan untuk menjadi Sungkan untuk kelas atas dan orang tua dan itu tidak dapatditerjemahkan.Kata kunci: Rasa hormat, etiket, sungkan, sopan santun.